Sigortacılık sisteminde aktif- pasif yönetimi ve Türkiye hayat sigortası örneğinde portföy performansının boyutlarını belirleyen faktörlerin irdelenmesine ilişkin bir model denemesi - Doğan, Ali İhsan (My University, 2001)
Sigorta sektörü, ulusal ekonomilerin vazgeçilmez kaynaklarından birisi olup yarattıkları fonlarla ülke ekonomisine küçümsenmeyecek boyutlarda katkıda bulunmaktadırlar. Dolayısıyla, ekonomide üretkenliği artıran ve etkin roller oynayan, böylece büyüme ve gelişmeyi destekleyen ekonomik işlevler sigorta şirketlerine finansal kurum olma özelliğini kazandırmıştır. Sigorta şirketlerinin aktif kalitesi ödeyebilirliğin korunması açısından oldukça önemli olup aktif kalitesi gelir getirme gücünü belirlemektedir. Bu nedenle, aktifler iş hacminin gerektirdiği yeterli büyüklükte olmalıdır. Sigortalıların haklarının korunabilmesi, likit ve aktif varlılığı yeterli sigorta şirketleri ile mümkün olabilecektir. Sigorta şirketlerinin mali yeterlilikleri, bir şirketin tüm sorumluluklarını karşılayabilecek düzeyde varlığa sahip olduğu şeklinde tanımlanmaktadır. Tüm dünyada oluşan küreselleşme eğilimi ve liberal hareketler sigorta şirketlerinin son 20 yıllık dönemde önemli gelişmeler yaşamasına neden olmuştur. Bu değişimlerden ve yeniden yapılanmalardan avantajlı çıkmak isteyen sigorta şirketlerinin uzun vadede varlıklarını sürdürebilmek amacıyla finansal yapıya daha fazla önem vermelerine neden olmuştur. Küreselleşen Dünya ekonomisi içinde, sigorta sektörünün oluşturduğu güçlü imaj, konsolidasyon faaliyetleri ve teknik sonuçları ile daha da sağlamlaşmıştır. Yeterli büyüklüğe erişmiş finansal örgütlerdeki sigorta şirketleri, her yıl en az % 15 reel olarak büyüyebilmektedir. Ülkemiz sigortacılığı oldukça yüksek bir dinamizm sergilemekte ve sigorta sektöründe yaşanan hızlı değişimler ülke ekonomisindeki gelişmelere paralel olarak hızla artarak reel olarak % 25 büyüyebilmektedir. Yüksek reel büyümeye rağmen, kapitalde ciddi bir artış gösteremeyen şirketler belirli dönem sonra mali yeterliliğini yitirme olasılığı ile karşı karşıya kalmaktadır. Şirketlerin rezervlerini prim üretimindeki yüksek artışı karşılayacak oranda artırması gerekmektedir. Prim üretiminde hiç artış göstermeyen veya yüksek sıçrama kaydeden şirketlerin bu artışın yerini tıkanıklığa bırakması halinde mali yetersizlik baş göstermektedir. Mali yeterliliği etkileyen önemli unsurlardan biri olan karlılık, teknik sonuçların ve mali gelirin kötü olduğu dönemlerde mali yeterlilikte kötü olarak etkilenmekte ve mali yetersizlik oluşmaktadır. Bu nedenle, şirketlerin daha iyi kapitalize olmaları, risk primini iyi tespit etmeleri, yatırım gelirlerini artırmaları ile birlikte bilanço karının dağıtılmayarak yeni sermaye artışı yoluyla özkaynak sağlama yönünde kullanılması ile mümkün olmaktadır. Risk teorisinin en önemli unsurlarından olan serbest rezervler ne olursa olsun uzun vadede risk primi yüklemesi yapamayan şirketler mali yetersizliğe düşmektedirler. Serbest rekabet sigorta pazarının reel olarak büyümesinin önkoşuludur. Şirketlerin yaşadığı makro ekonomik gerçekler belirli bir büyüklüğe erişmesini engellemektedir. Likidite sıkıntısı yaşayan şirketler, düşük kalitede verilen hizmetler, yoğun rekabet koşullarıyla birleştiğinde, risk primi yüklemesi yapmaksızın nakit amaçlı yazılım faaliyetine gitmekte ve mali yetersizliğe düşmektedir. Sigorta Şirketlerinin değerlendirilmesi yapılırken, Şirketlerin makro ekonomik gerçekleri dikkate alınarak prim üretimi, yatırımları, tazminat ödemeleri, yeterlilik marjı, reasürans politikası ve karlılığını dikkate almak gerekmektedir. Likidite zorluğu çeken şirketlerin sabit varlıklarını ve özkaynaklarını devreye sokması mali yetersizlik olarak adlandırmak gerçekçi olacaktır. Başlangıçta, şirketlerin yükümlülüklerini karşılayabilmesi risklerin doğru tespitine ve fiyatlandırma ile mümkündür. Daha sonra yatırımlar ve yönetim sözkonusu olmaktadır. Makro ekonomik yapı içerisinde faaliyet gösteren hayat sigorta şirketlerini yüksek enflasyon olumsuz yönde etkilemektedir. Yükümlülük karşıla yeterliliğindeki dalgalanmalar, tazminat ödemelerindeki, yatırım gelirlerindeki ve prim üretimindeki belirsizlikten kaynaklanmaktadır. Bu belirsizliklerin arkasında, ekonomik resesyonlar, enflasyon, yatırım oranlarında ve aktiflerin değerinde meydana gelen hareketlilik gibi faktörler yer almaktadır. Sigorta şirketlerinin sigortacılık faaliyetleri sırasında uyguladıkları politikalar mali bünyelerini yakından ilgilendirmektedir. Fiyatlandırma, saklama payı (konservasyon), reasürans politikası, tahsilat, kar dağıtım politikaları, sigorta şirketlerinin sigortacılık faaliyetlerini dolayısıyla mali gücünü etkileyen en önemli faktörlerden sayılmaktadır. Ülkemizde 15 civarında sigorta şirketinin mali yetersizlik içinde olduğu (Sigorta Murakabe Kanununun 20.maddesi kapsamında) ve bu şirketlerden 4 adedinde çok ciddi sorunlar yaşandığı bir gerçektir. 539 sayılı Kanun Hükmünde Kararnamenin ve Sigorta Murakabe Kanununun bazı maddelerinin Anayasa Mahkemesince iptal edilmiş olması, kanunda boşluk yaratılmasına neden olmuş ve sigorta şirketlerinin denetiminden istenilen sonuç alınamaz hale gelmiştir. Öncelikle etkin düzenleme ve denetim sağlayacak bir kanunun çıkarılması gerekmektedir. Özellikle, Avrupa Birliğine sürecinde, serbest ticaret imkanlarının ortaya çıkmasıyla yabancı sigorta şirketleriyle yaşanacak olan rekabet, stratejik bir konu haline gelecektir. Bu nedenle, yaşanacak stratejik değişimler ülkemiz sigorta şirketlerinin mali yeterlilik konusunun daha da önem kazanmasına neden olacaktır. Şirket'in üzerinde tuttuğu risk tutarı ile yazılan net prim arasında belli bir oran gözetilmeli, yazılan net prim miktarı yüksek düzeyde olan şirketlerin ancak yüksek oranda risk taşımalarına müsaade edilmelidir. Yüksek oranlı konservasyon yüksek tutarlı yazılan net prim miktarı ile mümkündür. Mali yeterlilik konusunda belirli oran tespit edilmeli, bu orandan önemli sapmalar mali yeterlilik konusunda ciddi sorunlar olduğunun ve şirketin ciddi bir

kaynak yetersizliği içinde olduğunun göstergesi olmalıdır. Öz kaynağı yetersiz olan şirket, öz kaynak ile orantılı, yani düşük ölçekli üretimde bulunmak yerine, reasürans yoluyla yetersiz öz kaynağa rağmen yüksek düzeyli prim üretiminde bulunmaktadır. Şirketin yetersiz öz kaynağa rağmen reasürans işlerinden yaralanmak suretiyle, yüksek düzeyli üretimde bulunması, şirketi önemli ölçüde reasürörlere bağımlı kılacak, bu durum birçok olumsuzluğu beraberinde getirecektir. Şirketin uzun vadede sağlıklı bir şekilde faaliyette bulunabilmesi, ancak güçlü bir öz kaynak yapısı ile mümkün olacaktır. Şirketin çalışma sermayesinin eksi bakiye vermesi, şirketin kısa vade de tahsil edilebilir alacaklarının kısa vadeli borçlarını karşılayamaması, hatta, şirketin kısa vadeli yükümlülüklerinin kısa vadeli alacaklarını aşması anlamına gelmektedir. Bu durumda şirketin, özellikle sermaye artırımı yapması, acentelerden olan alacaklarını ivedilikle tahsil etmesi gerekmektedir. Şirketin herhangi bir önlem almaksızın üretime devam etmesi durumunda cari aktifler ile cari yükümlülükler arasındaki fark giderek açılacaktır. Her işletmede olduğu gibi, sigorta şirketinin de bir amacı bulunmaktadır. Aksi takdirde işletmeden söz etmemiz mümkün olmayacaktır. İşletme politikası gereği iktisadi amaç, mal ve hizmet üretmektir. Bir sigorta şirketinde ise poliçe satın almak isteyen müşterilerine, riski en iyi şekilde ve yasal ve idari düzenlemelerin tespit ettiği fiyatlarla sağlamak önem arzetmektedir. Çünkü, en dar anlamıyla işletmenin iktisadi amacı ve fonksiyonu kar elde etmektir. Kar, bir işletmenin hiç şüphe yok ki başarısının da bir ölçüsüdür. Likiditenin zayıflaması ve bir ödeme güçlüğü içerisine düşme, portföyün daralması riskine karşı kar, bir tür primdir. Ayrıca, gerekli sermayenin tesisi yönünden de kar önemlidir. Sigorta şirketinin denetiminde ilk planda akla gelen, işletme içindeki risk ve zarar kaynaklarının saptanması ve olumsuz kaynakların ortadan kaldırılması için gerekli tedbirlerin alınmasıdır. Özellikle bir çok ülkede, hayat sigortalarında faaliyette bulunan sigorta şirketlerinin mali yeterliliği ile ilgili olarak bir çok önkoşullar ihtiva eden talimatlar yayınlanmıştır. Mali yeterlilik marjı ile ilgili incelemelerde, mali yeterlilik marjının ne olduğu, mali yeterlilik marjının hesaplanmasında hangi hedeflerin takip edildiği, işleyiş şeklinin nasıl olduğu, mali yeterlilik marjı ile benimsenen hususların neler olduğu ve mali yeterlilik marjının şirket politikasına etkisi ön plana çıkmaktadır. İşletme faaliyetlerinin devamlılığı ve sorumlulukların yerine getirilmesi sigorta şirketlerinin temel politikası olmakla birlikte mali imkanlarla bunların desteklenmesi de sigorta şirketlerinin klasik bir görevidir. O halde mali yeterlilik marjı yalnız kanunun öngördüğü hususların yerine getirilmesi ile ilgili olmayıp, özellikle işletme iktisadı yönünden önemi çok büyüktür. Diğer taraftan, işletmenin devamlılığı ve emniyeti için, mali yeterlilik marjının çok yüksek bir oranda tayin edilmesi durumunda, bu marj mali yapıda çeşitli problemler yaratacaktır. Bu nedenle, bir sigorta şirketi için öyle bir mali yeterlilik marjı tesis edilsin ki, şirketin öz sermayesi, yükümlülüklerini ve taahhütlerini azami nispette karşılayabilsin. Günümüzde yönetim son derece güç bir işlev haline gelmiş bulunmaktadır. Bunun önemli nedenlerinden biri, toplumun ihtiyaç duyduğu, mal ve hizmetleri üretmek için örgütlenmiş bulunan işletmelerin daha da büyümesi ve karmaşıklaşmasıdır. Gittikçe karmaşıklaşan ve yaşam koşullarının her geçen gün değiştiği toplumlarda, işletmelerin varlığını sürdürmek görevini üstlenmiş yöneticilerin vermek zorunda oldukları kararlar da aynı ölçüde zorlaşmaktadır. Çünkü, bu günün hızla değişen toplumunda yönetici, karar verme sürecinde bir takım belirsizlik durumu ile karşı karşıyadır. Konunun çok geniş şekilde ele alınmasının nedeni, Avrupa Birliği ülkeleri ile diğer ülke uygulamalarının irdelenmesi ve dünya uygulamasının da genel eğilimleri tespit edilerek makro anlamda dünya standartları ile entegrasyon sağlanabilmesi için gerekli kriterlerin tespitine yardımcı olması, Türkiye için sağlıklı sonuçlar verecek model önerisi geliştirilmesidir. Çalışmanın birinci bölümünde sigorta şirketlerinin sosyo ekonomik açıdan gelişmişlik düzeyine koşut olarak ekonomideki yeri, sigorta endüstrisinin ekonomik kalkınma ve ülkenin gelişim sürecinde etkin rol oynaması açıklanarak, sigortacılık faaliyetinin ülkemizde ve Dünyadaki yeri değerlendirilmiştir. Sigorta şirketlerinin, stratejik planlama sisteminin etkin bir yönetim aracı olması konusunda işletme fonksiyonlarının şirket içi ve şirket dışı faktörlerinin, aktif ve pasif yapısının değerlendirilmesi, erken uyarı sistemi kapsamında likit varlık değer performans öğelerinin tespiti ve sigorta şirketlerinin ve bankacılık sisteminin risk perspektiflerinin karşılaştırılarak flow chartlarının hazırlanması ikinci bölümün konusunu oluşturmaktadır. Bu bölümde, sigorta şirketlerinin stratejik planlamada işletme fonksiyonlarının önemi, aktif ve pasif yapısının mali tablolar yardımıyla mevzuat açısından değerlendirilmesi, Türk sigorta şirketlerinin Avrupa birliği açısından geldiği nokta, Türk sigorta sektöründeki düzenlemelerin hangi temel noktada sapma gösterdiği bu sapmaların hangi yöntemlerle giderileceği konusu irdelenmektedir. Çalışmanın üçüncü bölümünde, sigorta şirketlerine ilişkin aktif-pasif yönetim modelleri ile literatürün ayrıntılı bir değerlendirilmesi yapılmış olup aktif-pasif yönetimi ile ilgili Türk literatüründe mevcut olan çalışmaların genel bir değerlendirilmesi yapılarak uygulanabilirliği konusu ve sigorta şirketlerinin yatırım faaliyetleri incelenmiştir. Çalışmanın dördüncü bölümünde sigorta şirketlerinin finansal tablolar analizi, analizde kullanılan rasyolar, Ülkemizde uygulanan sistem ile Avrupa Birliliği ülkeleri ve Dünya uygulamaları karşılaştırılarak yöntemler analiz edilmiştir. Çalışmanın beşinci bölümünde Türk sigorta şirketlerinin performans galalarının oluşturulmasına yönelik model tasarlanmış ve sistem yaklaşımı olarak adlandırılan ve karmaşık sistemlerin analizinde kullanılan simülasyon yardımıyla Türk sigorta sektörünün duyarlı olduğu sermaye yapısı etmenlerinin boyutları hipotezler geliştirilerek 1988-1999 yılları arası faaliyette bulunan 34 hayat sigorta şirketinin mali sonuçları regresyon analizi,faktör analizi, t-test, diskriminant analizi ve varyans analizi kullanılarak irdelenmiş ve sektörün bu günkü durumu görülmüş ve gerekli saptamalar yapılarak Dünyada uygulanan mali yeterlilik analizleri karşılaştırılarak geleceğe ilişkin öngörüler oluşturulmaya çalışılmıştır. Altıncı ve son bölümde, modelin ekonomik sonuçları değerlendirilerek, Dünyadaki gelişmeler de dikkate alınarak ekonomik modelin sonuçları ışığında Türk sigorta şirketleri için ileriye yönelik öneriler geliştirilmeye çalışılacaktır. SUMMARY Turkey is experiencing rapid developments in the insurance sector, no significant academic work is available regarding the dynamics of capital adequacy in the Turkish insurance sector. Firstly, a research regarding this area seems extremely important for regulatory authorities. Secondly, it seems an important endeavor for the insurance industry itself in term of the financial theory's perspective of growth and planning process. This research is concerned with assessment of the financial strength of insurance enterprises of various kinds. This is the concern to shareholders, supervisory authorities, management, policyholders, potential investor and financial analysts are among those who require information about it. The social goal of the insurance industry is to make available adequate insurance protection on an affordable basis for all economic entities that desire such coverage and simultaneously earn an adequate profit. Insurance sectors have played prominent role in national economics and have helped create funds for giving help to economics that are not looked down. Insurance companies have distinguished themselves by providing fund for investment, increase productivity and have an active role in economics and in this way, prop up economic process. All of these degree, insurance companies have being throughout the consequences of their own success and they made them financial institutions. The movement towards to became spherical and liberal activity made impose greater developments on insurance company in last 20 years in the world. Maintaining a high degree of financial security is of prime importance for any insurance company. Insurance companies have played prominent roles in the world and companies are to remain financially strong because of consolidation activity and technical results. In the developed financial organization, insurance companies can be growing up % 15 every year. Our insurance sectors also grow up %25 parallel with economical. The solvency of an insurance company may be a matter of company low, as in the case where a company discloses that it has insufficient assets to meet its liabilities. An insurance company's management is faced continually with the task of reconciling two conflicting interest: those of its policy holders are interested in financial strength and thus expected the company to have a high rating by the rating agencies. Shareholders, in contrast, are more concerned with a return on equity that is common surate with the risk inherent in their investment and thus higher than the return a risk -free asset. Strategic planning is the development of methods for influencing and controlling or shaping the future of the company, so that management is able to respond quickly to changes in the economic, political and social environment. Companies of all sizes and all purposes must learn to direct the strategic management process by engaging in strategic decision making. The term strategic management is used to refer to the entire scope of strategic decision making activity in an organization. Organization decision making is highly complex and managerial choices are far from trivial. The fact that people have hard time learning from real life experiences compounds the problem, especially when the decision and their consequences are separated in time and space. Asset quality of the insurance company is the most important to meet the outgoing to which it is committed in respect of its liabilities. Asset quality is determined insurance companies by income forces and will be sufficient to meet the company's obligations. That's way, solvency, claim competence, management of insurance company is the most important and has to also utilize their capital effectively. Asset-liability management provides a framework for assessing and managing these risk exposures systematically and efficiently. Asset and liability values are influenced by risk factors other than interest rates as well. These factors forge links between asset and liabilities fundamental to the overall risk of an organization. The concept of the matching of assets to liabilities is fundamental in matters of finance. Matching is inherently connected with the uncertainty of future conditions, as measured by such indicators as rates of interest, inflation and currency exchange. Actuarial calculation is important that the nature of a portfolio that minimizes these risks be appreciated. Since it is concerned with the essential dynamics of the business, it is ideally suited to use by the management of the company. We have described allows to management to explore different investment strategies with a view to evaluating the return on capital available and the associated degree of risk. It needs to be emphasized that in making financial decision, we are no longer concerned with the static situation of a company's assets and liabilities at a particular point in time and how these will run off. It is important to realize that the conditions simulated bear a relation to potential managerial control. By carefully coordinating its management of assets and liabilities, a financial institution can operate more soundly and profitability. This coordinating is known as asset-liability management. Among the asset-liability management techniques in use is an approach known as dynamic financial analysis. Asset-liability management is the practice of managing a business so that decision on asset and liabilities are coordinated; it can be defined as the ongoing process of formulating, implementing, monitoring and revising strategies related to assets and liability in an attempt to achieve financial objectives for a given set of risk tolerances and constraints. Integrated asset-liability management, a new management perspective that is involving at the more innovative financial intermediaries in response to problems caused by the older functional management perspective. The new management perspective, termed asset- liability management call for an organization structured into integrated units that include all the functional activity related to life of business. Modern asset and liability management involves, continually, monitoring the existing position of a life insurance company, assessing how this differs from what is desirable and undertaking transaction to more the insurance company towards the desired position. In general sense, insurance company have always had to make decisions as to the liabilities they able to create and the assets they would acquire. The assessment of an insurance company's financial strength has been based on accounting statement that may be made concerning the company's ability to meet the company's obligations. The purpose of the statement of cash flows is to identify the sources and uses of cash during the year. Notice that this statement, like the income statement and statement of changes in owner's equity, is for a period of time Notice also the three activity categories: operating activities, investing activities and financing activities. Return on equity is a special case application of the rate of return concept. ROE is important to current stockholders and prospective investors because it relates earnings to the owner's investment, that is, the owner's equity in the asset of the entity. Financial strength is adopted more generally in respect of the insurer's financial capacity to meet adverse fluctuations and other risks. The maintenance of the financial viability of an insurance company is one of the basic concerns of management. For this purpose it is necessary for management to get reliable idea of the true financial position of the company and of the various risk that may jeopardize it. Asset risk management system have become on important management tool to steer asset portfolios in insurance industry. However, the reliable risk assessment of liabilities is also crucial for a company's financial security. The risk adjusted capital approach present us with a complete picture of the risk portfolio of an insurance company, comprising all the different types of care business risk. In looking at the financial strength of an insurance company we are concerned with the probability that the company has sufficient funds to meet its liabilities when fall due. If the payment pattern of the company's liabilities were known exactly, it would be possible to arrange its asset in such a way that the stream of income generated by those assets would much outflows of liabilities. The goal is to maximize the value of the insurance firm. The first step is to develop the right objective function to measure the life insurance's value. Second step is to use the objective function to identify and quantify the risk to which the firm is exposed. The third step is to use the objective function to analyze proposed strategies to maximize the value of the firm relative to risk. The insurance company can be capitalized by determining correctly the pricing of insurance contracts, increase the investment return and adding the balance sheet profit as a new capital. Concepts of liquidity, leverage, profitability and growth are as appropriate in insurance industry as elsewhere. The capitalization rate must be specified for calculating of the cash value of the forecast annual earnings surpluses. Within the scope of company valuation this serves on the one hand in discounting the sums to be distributable at the different times by the company on the valuation cut-off date and on the other in facilitating a comparison with alternative investments via the capitalization rate. The accounts of a life insurance company are not drawn up in such a way as to bring out the uncertainties involved in making an assessment of a company's financial strength or of its future profit - earning capacity. Financial analysts attempt to infer the position and from careful examination of successive years' account and the more detailed information available in returns to supervisory authorities. Measuring financial performance of a life insurance company and producing information to highlight the products, functions or business divisions which are performing well or badly is not an easy task. In the valuation of companies the net asset value has been the subject of many controversial discussion, both in literature and in practice. Net asset value is in general understood to mean the sum of the asset with their replacement values after deduction of debts. Although this is always a full reproduction value, due to the difficulty of recording and valuing intangible assets a part reconstruction value is often determined in practice. Even if the net asset value is only an auxiliary value, this calculation can not be limited to the part reconstruction value in the valuation of an insurance company because in insurance companies the intangible assets which are self-created or acquired at a large represent a considerable value even if they are in part not shown in the balance sheet. The claim function is critical in properly performing the contractual promise to indemnify the insured for a covered loss. Regulators increasingly favored enforcing capital requirements that rise with an intermediary's holdings of certain risky assets, apprising risky assets according to their market values, and imposing prompt remedies when capital ratios become to law. The companies have developed a corporate planning process in which premium levels, volumes of business and profitability, and an attempt is made to fallow this through to examine the impact on the balance sheet and future profits. An analysis of the emergence of profit and the balance sheet implies the ability in which the various items in the profit and loss account and the balance sheet. In collective risk theory the emphasis is on the probability that the company becomes insolvent or on its complement, the probability that the company remains viable. Analytical work this area deals most often with the probability of remaining solvent in an indefinitely long time period. To obtain an indication of the effects of constant margins on the solvency measures, simulations were run under conditions that would be expected to provide some insolvencies. The scope of this research is to review the financial operation of life insurance companies in order to detect variables, which will be helpful in identifying potential insolvency. The process of examining the entire financial position of an insurance company over time, considering both the interrelationships among the various parts and the stochastic nature of factor that can affect the results. The principle goal of the insurance sector is to safeguard claimants, policyholders, etc. engaged in financial transaction with insurers, from the fatal consequences of the insolvency of an insurer. Solvency is a concept that is often referred to but rarely defined. When it comes to definition most people would readily agree that being solvent implies having assets sufficient to meet the liabilities. However, assets and liabilities may be valued in different ways and attention must be paid to the timing of the various items. The solvency of the insurance company is regarded as a matter for the relevant supervisory authorities. The solvency of the supervisor is to regulate the insurance industry in such a way that consumers are protected from potential insolvencies of life insurance companies. The supervisor is consequently concerned with special case of the assessment of the capital adequacy of insurers. The regulations concerning the calculation of solvency margins and the level of assets needed to support them are contained in a number of official documents which cover both legislation which expand on the legislation. The regulators' interested and concerns often vary from those of other financial statement users, and in recognition of these special concern and responsibilities, statutory accounting principle have been established. In a regulatory context, an insurance company is solvent if its admitted assets exceed liabilities by a margin at least equal to the minimum capital required by law. In theory, an insurer is technically solvent so long as the value of its admitted assets less properly valued liabilities is at least to the required minimum capitalization. A solvent insurer collect premiums that realistically can be expected to satisfy anticipated loss settlements and meet all operating expenses; and maintains admitted assets sufficient to cover its existing liabilities, with a remaining safety margin that is at least equal to statutory net worth requirements. The analysis of the insurance company is mention in taking macro economic effects that are premium income, claim payments, investment, solvability, reinsurance policy capital gain and profitability. The insurance company lift premium rates in favour of growth in volume of business. The ability to precisely calculate an optimal capital and surplus level for new and continuing insurance companies would be beneficial to all parties concerned with their operation. Collective risk theory and profit maximization calculus provide some guidance for setting net worth levels and making decision involving alternative capital structures but these management tools are not without their limitations. Security offered through insurance products is based on the financial health and vigor of the insurance company that provides coverage. Managers of insurance companies have the first line responsibility for solvency maintenance and must operate the company in a manner that is consistent with achieving this objective. A central concept of this research is that the subject of financial solidity within the insurance industry can be dealt with in terms of one integrated model, which is applicable to all types of insurance operation. Insolvency can be defined as the state, which exists when cash inflows from assets are no longer adequate to meet the required outflows for liabilities. This model is derived from the basic principles of risk theory and is stochastic rather than deterministic. This research brings financial economics to bear on various aspect of solvency analysis. In the firs time, the traditional accounting approach to solvency measurement. Although the research represent an important step towards the development of a fully integrated approach to modeling the insurance firm. The models presented elsewhere in the working provide the level of institutional and statistical sophistication needed to arrive at an operational model of insurance enterprise. Market value accounting is the next step in the regulatory evolution that has produced dynamic solvency testing and scenario testing in Canada. Stochastic- dynamic modeling can be extended to meet the special needs of long term analysis of life insurance company to provide concrete support for the evaluation of the financial strength, and amaong other things, to answer other questions about the adequacy of the safety margins. A number of companies have developed a corporate planning process in which assumptions are made about future premium levels, values of business and profitability and an attempt is made to fallow this through to examine the impact on the balance sheet and future profits. An analysis of the possible emergence of profit in future years and the development of the balance sheet, implies the ability to model the way in which the various items in the profit and loss account and the balance sheet will behave in uncertain condition. Using simulation model, some of the uncertainty inherent in both the assets and the liabilities and compare the impact of alternative assumptions about the business that has been written and assets held. Each simulation gives rise to e realization of asset values, yields and retails price changes. It also produces a set of random variables which are used to determine the company's premium levels and the claim outgo in each successive year for which the business is projected. The main objective of this research is to construct an interactive dynamic simulation model on which the strategic management of an insurance company, concerning interaction between departments of the company, those between the company and the market and the related strategic decisions can be analyzed and certain policies for sustaining growth can be tested. More specifically, the model focuses on long term, strategic management problems that are naturally dynamic and persistent. The model generates many performance measures concerning the financial, technical and market aspects. The model provides a research platform for the theory of strategic decision making for the practice of scientific management. Techniques developed by actuaries for analysing profit have been primarily developed to support the actuarial valuation, which in turn is better suited to demonstrating solvency than determining profit. The analyses traditionally produced to not naturally provide the general management with the information required to manage business for profit maximization in the same way as would be considered normal in many other industries. This working describes how traditional actuarial techniques for analysis can be extended and adapted to apply to modern concept of profit for life insurance business. The analysis are performed through the use SPSS program and include regression analysis, factor analysis, t-test, discriminant analysis and variance analysis. The research is based on 36 life insurance company. The data used in the analysis is obtained from financial statements of the insurance company for the period 1988-1999. Insurance Company must satisfy minimum capital and surplus requirements and invest their assets within constraints imposed. The relation between size and capital structure has been an important research. Several hypotheses are developed to explain the determinants of capital structure of life insurance companies. We attempt to explore several financial variables that affect the corporate dept policies for Industrial Corporation at the insurance industry. The finding of the research provide evidence for a positive relation between the degree of operating leverage and dept level. High business risk is compensated by low levels of leverage as revealed by the negative relation between dept level and coefficient of variation in direct premium. High rate of inflation and growth pressures on the firm increase the need for additional financing. The risk of large insurance company with higher operation costs is magnified by the increase in the degree of financial leverage. Insurance company in low leverage group have higher growth rate, higher profitability and higher business risk due to variation in direct premium. The positive effect of leverage on return on equity is off set by high costs of debt financing which is frequently above the rate of return generated by the insurance company. With the earning valuation method the value of a company arises in financial terms from the future profit which the company will produce in future due primarily to its existing material assets at the time of valuation, its innovative force, its product design and position on the market, its internal organization and organizational management. The high level of inflation and uncertainty of interest rates force the insurance company to rely more on equity financing, internal and external. Moreover, the increasing need for working capital under inflationary condition lead the companies to rely more on short-term financing. The result of the research reflects the consequences of the economic conditions prevailing in insurance sector. High rate of inflation and growth pressures on the firm increase the need for additional financing. Uncertainty in the business environment, recession or other factors leading to a decline in demand for products of such companies decreases the earning near or below the break-even levels where the degree of operating leverage is magnified. The adjusted past and present result provide an orientation in relation to earning power as at the valuation date. The earning power as at the valuation date should generally be determined from the performance of the most recent representative accounting periods. As far as possible, profitability analyses of individual products and products areas and individual analyses of cost and revenue tendencies should be undertaken as a basis for the formulation of forecasts and projection. The further projections extend into future, the less concrete are the factors on which they are based. Financial strength of insurance companies has concentrated exclusively on the amount of capital required to support a given value of business. Model used must be dynamic, in sense that it takes account of future new business. In recent years, Canadian and England insurance companies have adopted alternative accounting methods such as dynamic financial analysis methods on solvency of insurance company especially operation of a life office. The minimum level of means to cover adverse fluctuations, the level of net retention and the minimum safety loading are involved, as well as methods of estimating the true financial position and of drawing realistic conclusions about the future prospects. The future financial data are estimated on the basis of five-year financial statements of firms. The model is designed to enable the user to compare the outcome on a number of different sets of parameters in order to determine the sensitivity of the results to particular aspects. Parameters need to chosen carefully in combination in order to produce realistic scenarios; it is intended that future versions of the program will provide for further linkages. There are a number of other parameters in the model which are developed which changes in the value of the direct premium, interest rate, mortality and morbidity, claim payments, conservation, general expenditures, personnel and management expenditures, tax payments and policy of the profit dividends. Several scenarios are developed to explain the determinants of capital structure of life insurance company. Parameters which are assets, technical reserves, term profit and equity from the sensitive function of life insurance companies, adopted accounting methods such as dynamic financial analysis methods. The model is used in many ways, which can measure the impact of alternative economic scenarios on the company and investigate the effects of different postulated future scenarios.
Keywords: Portföy Yönetimi; Sigorta; Sigortacılık_Hayat Sigortaları